Language Documentation The case of the Kelabit Language - Universiti Malaysia Sarawak, Institute of Social Informatics and Technological Innovations (Universiti Malaysia Sarawak (UNIMAS), 2015)
Talk by by Charlotte Hemmings,a PhD student from the School of Oriental Studies, University of London. The presentation, entitled “Language Documentation: The case of the Kelabit Language” addressed the key elements of language documentation such as the creation, annotation, preservation and dissemination of transparent records of a language.